Short and frequent skin contact with nickel - Erfani, Behnaz; Lidén, Carola; Midander, Klara (Contact dermatitis, 2015)
Summary Background The existing EU nickel restriction does not sufficiently protect the population from skin exposure to nickel. Better understanding is needed of the extent to which short and frequent contact with nickel‐releasing items contributes to nickel deposition on skin. Objectives To quantify nickel skin exposure from short and frequent contact with nickel‐releasing materials. Materials/methods Sequences of short contact events were assessed in (i) touch tests for measurement of nickel skin dose, (ii) wipe tests to similarly quantify the nickel release during a touch, and (iii) immersion tests in artificial sweat, for nickel‐containing alloys and pure nickel. Results Nickel skin doses from a single touch were 0.024–4.7 µg/cm2 for all materials. Touching or wiping five untouched surfaces resulted in more accumulated nickel than five repeated touches of the same surface. The released amounts of nickel were generally lower at immersion, but increased with the number of repeated immersion periods. Conclusions Nickel skin doses were quantified after one single touch for all study materials. Touch tests, and potentially wipe tests as a proxy for skin dose measurements, are preferred to immersion tests for the assessment of short and frequent skin contact with nickel.